2017
DOI: 10.1590/1807-1929/agriambi.v21n6p421-426
|View full text |Cite
|
Sign up to set email alerts
|

Senna multijuga and peat in phytostabilization of copper in contaminated soil

Abstract: Phytoremediation is a technique that uses plants, whether associated or not to ameliorating agents, for phytostabilization of contaminated soil. The aim of this study was to evaluate the use of Senna multijuga associated with peat in the phytostabilization of copper contaminated soil. The experiment was carried out in a greenhouse for 120 days, using an entirely randomized design in a factorial arrangement (2 x 6), with and without peat (200 mL L-1 soil) and six doses of copper (0, 60, 120, 180, 240, 300 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…H.S. Irwin & Barneby) Fabaceae (De Marco et al, 2017), corroborating with the results found in this study for plants without inoculation. Mycorrhizas play a key role in reducing the toxic effect of Cu on the plant.…”
Section: Resultssupporting
confidence: 92%
“…H.S. Irwin & Barneby) Fabaceae (De Marco et al, 2017), corroborating with the results found in this study for plants without inoculation. Mycorrhizas play a key role in reducing the toxic effect of Cu on the plant.…”
Section: Resultssupporting
confidence: 92%
“…Conversely, Pimentel et al [79] found no effects of container type or season on root quality, total volume, or SSAR of yerba mate plantlets propagated by mini-cuttings. Similarly, Marco et al [80] have mentioned that incorporating peat into copper-contaminated soils improves plant qualities or quality indices, such as root dry matter, SSAR, stem diameter, the DQI, and the copper tolerance index, by improving the physical and chemical properties of the soil. These same authors found that a gradual increase in copper doses in the soil (300 mg of Cu kg −1 of soil) decreases the SSAR by 40% [12,80].…”
Section: Specific Surface Area Of Rootsmentioning
confidence: 99%
“…Similarly, Marco et al [80] have mentioned that incorporating peat into copper-contaminated soils improves plant qualities or quality indices, such as root dry matter, SSAR, stem diameter, the DQI, and the copper tolerance index, by improving the physical and chemical properties of the soil. These same authors found that a gradual increase in copper doses in the soil (300 mg of Cu kg −1 of soil) decreases the SSAR by 40% [12,80]. Generally, plants with a high SSAR show high tolerance to soils contaminated with heavy metals [81], perhaps due to defence mechanisms such as melanin accumulation in the roots.…”
Section: Specific Surface Area Of Rootsmentioning
confidence: 99%